(3GdGfOeGL hGdJMGdaGJ GdGSJQGJjLjI Hjf GdTQcGJ aj GdOhd GdYQHjI (B/s - (3GdYhVj, QaYJ GdSjOs; (3HSjhfj, GSeGYjd Ydj s ((3GdbGgQI(B: s (3GdefXeI GdYQHjI ddJfejI GdGOGQjI(B, s, 2005)
(3GdHjFI GdOhdjI GdeMaRI Ydi GdGfOeGL GVGaI Gdi GdGfOeGLHjf GdTQcGJ GdcHjQI aj GdJWHjb h cPG GdMLL GdeDjOI dGfOeGL GdTQcGJ aj GdYGde GdYQHj(B, (3GfOeGL GdTQcGJ aj GdHdGO GdYQHjI eY GSJQGJjLjI ebJQMI(B, (3cPdc HfGA GdJMGdaGJ GdGSJQGJjLjI GVGaI Gdi eRGjG h YjhH GdJMGdaGJ GdGSJQGJjLjI(B, (3GdOhd GdYQHjI h GdGfOeGL h GdJMGdaGJ GdGSJQGJjLjI h aj GdGNjQ fUGFM ddeOjQjf dJMbjb GdfLGM(B.s
(3eQGLY U(B.397s
Keywords: (3GdJMGdaGJ GdGSJQGJjLjIs; (3GdTQcGJ (B- (3GfOeGLs